Contextual Plausibility Effects Among Older Adults in Chinese Free-View Reading: Co-Registration of Eye-Tracking and Electroencephalography. - Lou, Longxia; Feng, Ximei; Liang, Zehao; Liu, Zhi-fang; Zhang, Zhijun (Perceptual & Motor Skills, 2026)
With regard to how aging affects contextual plausibility in Chinese natural silent reading, research remains limited. To address the methodological limitations inherent in using eye-tracking measures and event-related potentials separately, we aimed to apply co-registration of eye-tracking with electroencephalography (EEG) in Chinese natural silent reading. Old and young adults were asked to read sentences that contained either semantically congruent or semantically violated words. We failed to replicate any differences in contextual plausibility effects between the older and younger adults on eye-tracking measures of early word processing (including first fixation duration, gaze duration, probability of skipping, and refixation). However, larger plausibility effects for the old adult readers were observed in the measures of regression in probability and total reading time. No reliable age-related differences in plausibility effects were observed for brain response amplitudes in the parafoveal and foveal intervals (from −400 to 200 ms). Both eye-tracking and EEG data demonstrated that contextual plausibility in early word processing was preserved among the old adults, while the Chinese old adult readers made more efforts to reanalyze semantic information in relation to free-view reading.